Analisa Kecacatan Produk Menggunakan Metode Statistical Process Control (SPC) dan Failure Mode and Effects Analysis (FMEA) - Hardianto, Achmad Davit; Sulistiyowati, Wiwik (Ekonomis: Journal of Economics and Business, 2025)
The purpose of this study is to determine the causes of product defects and provide suggestions for improvement and find out how to control defects in product quality. The research method is carried out by combining 2 (two) methods, namely: Statistical Process Control and Failure Mode and Effects Analysis. The results show that the highest defects occurred in October 1,319 out of 154,800 bags and the lowest occurred in November 1,209 out of 144,900 bags. Types of defects, namely: imperfect sealing as many as 2,175 bags; loose stitches as many as 4,241 bags; and bulging bags as many as 1,169 bags. The analysis suggests improvements in production, worker skills, machine maintenance, SOP (standard operating procedures), and working conditions.